KARAKTERISTIK COMPUTER VISION SYNDROME PADA MAHASISWA YANG BELAJAR SECARA HYBRID DI PSSK FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA ANGKATAN 2020 - Maheswari, Putu Ayu Dessita (Essence of Scientific Medical Journal; Vol 21 No 2 (2024): Volume 21 No. 2 (Juli - Desember 2023) Essential: Essence of Scientific Medical Journal, 2024)
Introduction: The COVID-19 condition and the development of digital technology caused many daily activities changed to online activities, including learning activities. This can cause Computer Vision Syndrome (CVS) or Digital Eye Strain (DES). CVS is a collection of eye symptoms caused by digital screens. Method: This research is a descriptive study with a cross-sectional study design with a proportion estimation formula to calculate the sample size. Data collection was carried out using Google Forms. Data processing uses the SPSS version 27 application Result: There are 153 respondents. A total of 88 people (57.5%) experienced CVS, respondents who experienced CVS were dominated by female respondents 56 (63.6%), 59 people aged 21 years (67.0%), 47 people (53.4%) who used digital screens for > 6 hours, and 46 people who used glasses (52.3%). %). The most dominant symptoms were itchy eyes in 75 people (85.2%), sensitivity to light in 62 people (70.5%), and watery eyes in 66 people (75.0%). Discussion: CVS occurs due to excessive use of digital screens and is influenced by various factors, such as gender, age, duration of digital screen use, use of glasses, contact lenses, break frequency, lighting, ergonomic position, etc. Conclusion: Most students at PSSK FK Unud class of 2020 experienced CVS, especially women, aged 21 years, duration of use of digital screens > 6 hours, and used glasses. The most common symptoms are itchy eyes, sensitivity to light, and watery eyes.   Keywords : Computer Vision Syndrome (CVS), Digital Eye Strain (DES), College Students